Anionic vacancy-dependent activity of the CoSe2 with a tunable interfacial electronic structure on the N-doped carbon cloth for advanced Li–O2 batteries. Issue 32 (4th August 2020) - Hou, Zhiqian; Shu, Chaozhu; Zheng, Ruixin; Liu, Chunhai; Ran, Zhiqun; Yang, Tingshuai; Hei, Peng; Zhang, Qiang; Long, Jianping
Abstract : The inferior reversibility of the formation/decomposition of the lithium peroxide (Li2 O2 ) and its insolubility and insulation features result in poor energy efficiency and limited durability of state-of-the-art Li–O2 batteries. Abstract : The inferior reversibility of the formation/decomposition of the lithium peroxide (Li2 O2 ) and its insolubility and insulation features result in poor energy efficiency and limited durability of state-of-the-art Li–O2 batteries. Herein, we elaborately designed sisal-like CoSe2 nanowires enriched with Se vacancies (VSe -CoSe2 ) anchored on a scaffold of magnetron-sputtered N-doped carbon cloth (N-CC) to address the above challenges. The synergistic coupling of vacancy regulation with interfacial interaction can be used to tune the ability to adsorb active oxygen and intermediate species and enhance the interfacial electron transfer during oxygen redox reactions. Experimental results demonstrate that the VSe -CoSe2 @N-CC-based Li–O2 battery demonstrates a substantially decreased overpotential (∼0.56 V) and extraordinary durability (over 955 h). This work indicates that the synergistic coupling of vacancy modulation and interface interaction is a promising strategy for effectively enhancing the comprehensive performance of Li–O2 batteries, which provide prospective insights into the exploration of next-generation highly efficient metal–air batteries.